TIME ACCELERATION ANALYSIS USING THE TIME COST TRADE OFF METHOD ON THE WHEAT SILO AND PELLET SILO STRUCTURE REPAIR PROJECT PHASE III IN SURABAYA - Klau, Maria Junita; Sajiyo, Sajiyo; Tjendani, Hanie Teki (Transpublika Publisher, 2024)
The wheat silo and pellet silo structural repair project Phase III in Surabaya holds great significance for the wheat flour processing industry in Indonesia. PT Indofood Sukses Makmur Tbk Bogasari Surabaya Division, as one of the leading wheat flour producers, required structural repairs on both silos to ensure the smooth operation of the plant and the quality of the final product. Given the importance of time and cost in the success of this project, an effective approach to time and cost management was essential. The project necessitates proper project management to avoid delays and cost overruns, with a budget of IDR 28,011,000,000 and an estimated duration of 455 calendar days. This research employs the Time Cost Trade Off (TCTO) method to analyze options for accelerating project time by considering additional costs that may arise. Microsoft Project software is utilized to identify the critical path, allowing project managers to focus on activities with the greatest impact on the overall schedule. The results indicate that the critical path of the project includes activities such as mobilization and demobilization, administration and reporting, work safety, and repair of the old grain silo. By using TCTO, the project completion time can be accelerated to 359 days from 455 days, reducing the duration by 21.10%.